Communication Preferences of Florida Farm Bureau Young Farmers & Ranchers - Ricky Telg; Carly Barnes (Journal of Applied Communications, 2012)
The purposes of this study were to determine the Internet-based communication technologies and social media platforms Florida Farm Bureau Young Farmers & Ranchers use, as well as to evaluate their attitudes toward incorporating those communication methods within and from the Florida Farm Bureau Federation. Two focus groups were conducted with Florida Farm Bureau Young Farmers & Ranchers members. The organization consists of Farm Bureau members, ages 18 to 35 years. Results indicate that the focus group participants felt that social media and Internet-based communication should be utilized by the Florida Farm Bureau Federation and that by not doing so the organization could miss the opportunity to reach large audiences both within its own membership and in the general public. Respondents also expressed a desire for the organization to prepare its members to be proactive and share their story by providing online resources. Although the respondents expressed a need for the Florida Farm Bureau Federation to become more involved with utilizing social media and Internet-based communication, the respondents varied in levels of competency and comfort with those communication methods. The findings suggest that social media used by the organization should supplement existing communication channels, and satisfy younger members’ need for the organization to employ a stronger Web presence and make information readily accessible online both for internal and external audiences.
Keywords: Farm Bureau; social media; communication technology; young farmers